Service Delivery bagi Perempuan Korban Kekerasan Seksual selama Masa Pandemi Covid-19 di Kota Samarinda - Sari, Diana Fera; Kriswibowo, Arimurti (Universitas 17 Agustus 1945 Surabaya, 2021)
This study aims to find out how the service delivery provided to women victims of sexual violence during the Covid-19 pandemic in Samarinda City was identified based on 6 (Six) standard components of service delivery as stated in PANRB Ministerial Regulation Number 15 of 2014 concerning Service Standard Guidelines. This study uses qualitative methods with data collection through interviews, observation, and documentation. In determining the informants of this study using purposive sampling and snowball sampling techniques. Data analysis uses the concept of an interactive model. The results of the study show that the service delivery provided to women victims of sexual violence during the Covid-19 pandemic in Samarinda City includes 1) the existence of 6 main service products that are provided with due regard to health protocols, 2) free service fees, 3) the length of service time depends on client's condition, 4) service requirements consist of Identity Card (KTP), Family Card, marriage book, and birth certificate 5) service procedures have been listed in the UPTD PPA Samarinda SOP, and 6) during the Covid pandemic -19 complaints can be made indirectly via hotline 112, hotline 082324421313, and through the SIPPEKA application.`